Retinol and Retinyl Palmitate in Foetal Lung Mice: Sexual Dimorphism - Olga Carvalho; Carlos Gonçalves (Critical Care Research and Practice)
In this work, we evaluate the lung retinoids content to study the possible difference between male and female mice during prenatal development and to comprehend if the vitamin A metabolism is similar in both genders. The study occurred between developmental days E15 and E19, and the retinol and retinyl palmitate lung contents were determined by HPLC analysis. We established two main groups: the control, consisting of foetuses obtained from pregnant females without any manipulation, and vitamin A, composed of foetuses from pregnant females submitted to vitamin A administration on developmental day E14. Each of these groups was subdivided by gender, establishing the four final groups. In the lung of control group, retinol was undetected in both genders and retinyl palmitate levels exhibited a sexual dimorphism. In the vitamin A group, we detected retinol and retinyl palmitate in both genders, and we observed a more evident sexual dimorphism for both retinoids. Our study also indicates that, from developmental day E15 to E19, there is an increase in the retinoids content in foetal lung and a gender difference in the retinoids metabolism. In conclusion, there is a sexual dimorphism in the lung retinoids content and in its metabolism during mice development.